2Sin²x - 4SinxCosx + 1 = 0
2Sin²x - 4SinxCosx + Sin²x + Cos²x = 0
3Sin²x - 4SinxCosx + Cos²x = 0
Это однородное уравнение второй степени Разделим почленно на
Cos²x ≠ 0 , получим
3tg²x - 4tgx + 1 = 0
Сделаем замену tgx = m
3m² - 4m + 1 = 0
D = (- 4)² - 4 * 3 * 1 = 16 - 12 = 4 = 2²
![m_{1}=\frac{4+2}{6}=1\\\\m_{2} =\frac{4-2}{6}=\frac{1}{3}\\\\\\tgx_{1}=1\\\\x_{1}=arctg1+\pi n\\\\x_{1}=\frac{\pi}{4} +\pi n \\\\tgx_{2}=\frac{1}{3}\\\\x_{2}=arctg\frac{1}{3} +\pi n m_{1}=\frac{4+2}{6}=1\\\\m_{2} =\frac{4-2}{6}=\frac{1}{3}\\\\\\tgx_{1}=1\\\\x_{1}=arctg1+\pi n\\\\x_{1}=\frac{\pi}{4} +\pi n \\\\tgx_{2}=\frac{1}{3}\\\\x_{2}=arctg\frac{1}{3} +\pi n](https://tex.z-dn.net/?f=+m_%7B1%7D%3D%5Cfrac%7B4%2B2%7D%7B6%7D%3D1%5C%5C%5C%5Cm_%7B2%7D+%3D%5Cfrac%7B4-2%7D%7B6%7D%3D%5Cfrac%7B1%7D%7B3%7D%5C%5C%5C%5C%5C%5Ctgx_%7B1%7D%3D1%5C%5C%5C%5Cx_%7B1%7D%3Darctg1%2B%5Cpi+n%5C%5C%5C%5Cx_%7B1%7D%3D%5Cfrac%7B%5Cpi%7D%7B4%7D+%2B%5Cpi+n+%5C%5C%5C%5Ctgx_%7B2%7D%3D%5Cfrac%7B1%7D%7B3%7D%5C%5C%5C%5Cx_%7B2%7D%3Darctg%5Cfrac%7B1%7D%7B3%7D+%2B%5Cpi+n++++++++++++++)
Везде добавить n ∈ z